2011
DOI: 10.1177/0269881111400650
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of anxiolytic effects of the CRF1 receptor antagonist R317573 in the 7.5% CO2 proof-of-concept experimental model of human anxiety

Abstract: We have validated the use of prolonged inhalation of 7.5% carbon dioxide (CO(2)) as a human model of anxiety and have shown that drugs from two prototypical classes of anxiolytics, benzodiazepines and a serotonin reuptake inhibitor, attenuate CO(2)-induced symptoms (Bailey et al., 2007a). Preclinical evidence suggests that drugs acting at the corticotropin-releasing factor (CRF) system may be useful for the treatment of depression, anxiety, and other stress-related disorders (Valdez, 2006), hence we have now e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 19 publications
(28 reference statements)
0
43
0
Order By: Relevance
“…*po0.05, **po0.01, ***po0.001. a proof-of-concept study using 7.5% CO 2 to induce anxiety (Bailey et al, 2011). One possibility is that GSK561679 is anxiolytic in some tests but not in the NPU test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*po0.05, **po0.01, ***po0.001. a proof-of-concept study using 7.5% CO 2 to induce anxiety (Bailey et al, 2011). One possibility is that GSK561679 is anxiolytic in some tests but not in the NPU test.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CRF 1 antagonists may reduce responses to acute rather than chronic stress (Koob and Zorrilla, 2012). However, minimal research has examined this issue in humans (Bailey et al, 2011;Binneman et al, 2008), and the current study fills this gap by examining the effects of a CRF 1 antagonist GSK561679 (Verucerfont) on startle, a validated, cross-species marker, in healthy individuals (Grillon, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…A CRF 1 antagonist (R317573/JNJ19567470/CRA5626) also recently showed activity in rodent (Shekhar et al, 2011) and human (Bailey et al, 2011) panic models. These models reflect a dynamic, active response to an acute stressor and, from a face validity perspective, may reflect more the symptoms of specific subtypes of anxiety disorders rather than of generalized anxiety disorder.…”
mentioning
confidence: 99%
“…In a clinical model of generalized anxiety induced by 20-min inhalation of 7.5% CO 2 , preliminary studies in 12 healthy subjects showed that R317573 (40 mg once daily) given for 7 days significantly reduced panic symptom score and generalized anxiety compared to placebo. 194 Positron emission tomography (PET) studies indicated that the acute administration of R317573 at 30 and 200 mg results in dose-related changes in regional glucose metabolism in regions relevant to mood and anxiety disorders. 195 A recent clinical study using functional magnetic resonance imaging showed that an acute oral administration of CRF 1 antagonist, GW876008 (single dose of 20 or 200 mg orally) dampened the amygdala activation produced by the anticipation of visceral pain compared to placebo drug in IBS female patients.…”
Section: Does Targeting Corticotropin-releasing Factor Receptor Have mentioning
confidence: 99%